EJBM 2019
DOI: 10.7176/ejbm/11-14-09
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Style, Organizational Commitment, and Organizational Citizenship Behavior on Credit Union in Indonesia

Abstract: This study investigates the relationship between transactional and transformational leadership styles, organizational commitment, and organizational citizenship behavior (OCB) in the context of Credit Union. Respondents are 207 non-managerial employees of Credit Union in Indonesia. Data was collected by questionnaire and analysed by using SEM. The result shows that transformational leadership has positive effect on organizational commitment, and organizational commitment has effect on OCB-coworker targeted. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…Several studies (McLaggan et al, 2013;Guyo et al, 2019;Ramli et al, 2019;Alemayehu & Batisa, 2020;Ene, 2020;Khan et al, 2020) have revealed that a positive relationship exists between TLS and employee commitment. Conversely, studies by Cho et al (2019) as well as Wulani et al (2019) reveal that managers' TLS demonstrates a negative association with employee commitment. Despite the lack of harmony in research findings pertaining to the direction of the relationship between a TLS and employee commitment, Baloch et al (2014) insist that TLS, considered as a mono-construct, remains a strong predictor of employee commitment.…”
Section: Facets Of Tls and Employee Commitmentmentioning
confidence: 94%
“…Several studies (McLaggan et al, 2013;Guyo et al, 2019;Ramli et al, 2019;Alemayehu & Batisa, 2020;Ene, 2020;Khan et al, 2020) have revealed that a positive relationship exists between TLS and employee commitment. Conversely, studies by Cho et al (2019) as well as Wulani et al (2019) reveal that managers' TLS demonstrates a negative association with employee commitment. Despite the lack of harmony in research findings pertaining to the direction of the relationship between a TLS and employee commitment, Baloch et al (2014) insist that TLS, considered as a mono-construct, remains a strong predictor of employee commitment.…”
Section: Facets Of Tls and Employee Commitmentmentioning
confidence: 94%